Evaluation of the implementation of integrated design and build construction contracts based on LKPP Regulation No. 12 of 2021 based on contract management body of knowledge and risk minimizing dispute claims from the service provider's perspective - Namira, Al-Zahra Aisha; Latief, Yusuf (International research journal of engineering, IT and scientific research, 2024)
Infrastructure development in Indonesia is key to improving connectivity and equitable development, although it often faces project management challenges such as errors in contract documents that trigger disputes. The government has adopted the Design and Build method to accelerate construction and reduce design errors, but this method often creates more disputes than conventional methods. This study evaluates the implementation of the Integrated Design and Build Contract system in government projects based on LKPP Regulation No. 12 of 2021 and the Contract Management Body of Knowledge (CMBOK) 7th Edition, focusing on integrating contract management processes and risk analysis. Through questionnaires, expert interviews, and statistical data analysis, this study identified 10 significant high-risk risks, such as incorrect selection of design consultants, inaccurate cost estimates, and frequent design changes, although unidentified utility risks were not proven to be significant to disputes. The results of the study provide strategic recommendations to improve the effectiveness of the contract system, reduce disputes, and support the performance of infrastructure projects in Indonesia.